Will Transformational Leadership Style Increase Organizational Performance in MSMEs? A Systematic Literature Review - Bahri, Khoirun Nisa; Gaffar, Vanessa; Wibowo, Lili Adi; Dirgantari, Puspo Dewi; Rofaida, Rofi (Journal of Organizational and Human Resource Development Strategies, 2025)
To achieve MSME innovation and performance, leadership is crucial. Burns's divided leadership into transformational and transactional styles is one of the key theories of leadership. The purpose of this essay is to pinpoint the best leadership philosophies for enhancing SME organizational performance. This study included a methodical review of the literature. According to the study's findings, transformational leadership is thought to enhance organizational performance in SMEs. Contrarily, there is little evidence that the transactional leadership style improves organizational performance in SMEs. In conclusion, transformational leadership is more crucial than transactional leadership for enhancing MSME performance. These findings help MSME executives develop transformational leadership, which is focused on the charisma of the leader.